An author's guide to scholarly publishing - Derricourt, Robin M. (Princeton paperbacks., 1996)
"Directed specifically to the needs of academic authors, this realistic handbook is a guide to publishing success for both beginning and seasoned scholars. Robin Derricourt uses an immensely readable series of informal letters to provide a fund of practical advice: an up-to-date manual on how to plan and prepare a book, approach a publisher, secure a contract, and build a reliable author-publisher relationship that will last throughout the process of publication and marketing. Informed by rare common sense, and a sense of humor, the book speaks clearly about the most recent developments in the rapidly changing world of electronic publishing, clarifying what can and cannot be achieved with word processors. From the possible negative responses of a publisher to the questions implied by success - new editions and subsidiary rights - An Author's Guide to Scholarly Publishing is indispensable reading for academics in every field."--BOOK JACKET. "Derricourt's candid yet encouraging suggestions will be useful at any stage of book preparation, including the process of writing, when focusing on purpose and audience benefits both the author and the future publisher, not to mention the future reader! Furthermore, his "letters" include those on various kinds of books - standard monographs, technical books, conference volumes, edited volumes, collected papers, textbooks, and works built on dissertations. A reference of "nuts and bolts," this book is also quick and entertaining reading when pursued from cover to cover."--